BRAC health programme evaluation: a case study of labour colony panna textile, Khagan, Savar, Dhaka - Lin, Nay (BRAC University, 2015)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2014.